Metode Etnografi Dalam Penelitian Kualitatif - Mahendra, Arivan; Ilhami, Muhammad Wahyu; Nurfajriani, Wiyanda Vera; Afgani, Muhammad Win; Sirodj, Rusdy Abdullah (Peneliti.net, 2024)
Ethnographic research is one of the most important qualitative research in which the researcher observes or interacts with the target population and the researcher plays an important role in obtaining useful cultural information, and that is why ethnographic research is known as cultural ethnography or cultural anthropology. Ethnographic research can now be utilized in all fields including education. In this research, the method used is the library research method. The library study method or library (library research) can be defined as a series of activities related to library data collection methods, reading and recording and processing research materials. Ethnography as a research method has experienced developments such as the emergence of audience ethnography, digital ethnography, visual ethnography and others. With this development, ethnographic research design can be formed and developed according to the research context that will be made by a researcher. Ethnographic researchers become independent subjects in determining their research design. Although they still have to use existing theories then integrate them with the context of the research being made. The formation of the research design is entirely left to the researcher. There is no standardized form in ethnographic research such as quantitative research that has been measured. The interpretation of research results, ethnographers deal with human objects and cultures that also change. Subjectivity is unavoidable but can still be reduced by ethnographic researchers.